Effectiveness of Credit Management Policies as a Treasury Management Tool in Enhancing Financial Performance: The Case of Colcom Pvt Ltd. 2015-2019 - Mbano, Samson; Wadesango, Ongayi; Wadesango, Newman (International Journal of Economics and Financial Issues, 2022)
This study evaluated the viability of credit arrangement policies in enhancing financial performance of firms. The purpose of the study was to evaluate amongst other things, the effects of money receipting framework on monetary execution and the effects of enthusiasm on past due records. A logical exploration configuration was utilized in this investigation just as a multivariate relapse investigation was directed to decide the coefficients of the factors. The study adopted a quantitative research methodology and data was collected using a questionnaire. Judgemental inspecting method was utilized on a sample size of 11 representatives out of a whole populace of 20 workers. In addition, two top administration representatives were met for information sharing. The results indicated that the current credit administration strategies of Colcom Ltd were not completely executed and furthermore, they positively affected financial execution. The study concluded that credit arrangements had the best effect on budgetary execution, followed by some factors such as the economic instability and political interventions. This study recommends the full implementation of the current credit management policies, regular training of credit officers and to practice scientific credit control (application of risk evaluation techniques). This would improve their efficiency in credit analysis and customer analysis management to secure as much as possible their assets, and reduce the high chances of turning into credit losses and their negative effects on good financial performance.